Incorporating the erythrocyte sedimentation rate for enhanced accuracy of the global registry of acute coronary event score in patients with ST-segment elevated myocardial infarction: A retrospective cohort study. Issue 41 (9th October 2020) - Li, Chuang; Wang, Yuxing; Zhang, Qian; Wang, Lefeng; Li, Kuibao; Yang, Xinchun
Abstract : Abstract: There is scarce evidence that the erythrocyte sedimentation rate (ESR) could efficiently improve the prediction accuracy of the Global Registry of Acute Coronary Events (GRACE) risk score in cases of ST-elevation myocardial infarction (STEMI). A cohort of 1094 STEMI patients undergoing primary percutaneous coronary intervention was retrospectively recruited. Patients were categorized based on the ESR values. Final endpoints included cardiovascular death and major adverse cardiovascular event (MACE) occurrence. The predictive value of combined models with the GRACE score and ESR was assessed by receiver operating characteristic (ROC) analysis, net reclassification improvement (NRI), and integrated discrimination improvement. During the mean follow-up of 23 months, 34 patients died and 190 experienced MACEs, of which 23 patients died in the first year; both endpoints were more frequent in the higher group. The ESR and high-sensitivity C-reactive protein (hs-CRP) were independent risk factors of 1-year cardiovascular death, together with the GRACE score (ESR: hazard ratio = 1.03, P = .006 hs-CRP: hazard ratio = 1.00, P = .001; GRACE: 1.03, P = .012). Although no statistical improvement in the area under the ROC curve was observed in either the GRACE/ESR or the GRACE/hs-CRP model (GRACE/ESR models: 0. 8073 vs GRACE: 0.7714, P = .22; GRACE/ESR models: 0. 7815 vs GRACE: 0.7714, P = .61), the GRACE score and ESR together significantly improved the NRI (0.633; P < .001) compared with the GRACE alone. Regarding the mid-term mortality, adding the ESR to the GRACE score not only improved the NRI (0.8433; P < .001), but also increased the integrated discrimination improvement (0.0509; P = .04). The ESR is an independent risk factor of cardiovascular death and MACE in STEMI patients receiving primary percutaneous coronary intervention. The ESR comparatively enhanced the predictive values of the prognostic model, including the GRACE risk score.